2017
DOI: 10.4995/ijpme.2017.6807
|View full text |Cite
|
Sign up to set email alerts
|

Integrated production-distribution planning optimization models: A review in collaborative networks context

Abstract: Researchers in the area of collaborative networks are more and more aware of proposing collaborative approaches to address planning processes, due to the advantages associated when enterprises perform integrated planning models. Collaborative production-distribution planning, among the supply network actors, is considered a proper mechanism to support enterprises on dealing with uncertainties and dynamicity associated to the current markets. Enterprises, and especially SMEs, should be able to overcome the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Para que las empresas sigan siendo competitivas en sus mercados, deben revisar constantemente sus planes de producción, respaldados por estrategias que permitan mayores ganancias y rentabilidad (Romanzinil et al, 2017). Llevar a cabo una planificación de producción permite a las empresas mejorar su preparación y agilidad para enfrentar las turbulencias del mercado (Andres et al, 2017). La correcta selección de esta herramienta es de gran utilidad al incrementar los indicadores de producción, elevar el servicio que las mismas brindan al cliente (Tamayo y Urquiola, 2014) y emplear de manera más eficiente los recursos, sin afectar la calidad de los productos (Moreno y Reyes, 2015).…”
Section: Figuraunclassified
“…Para que las empresas sigan siendo competitivas en sus mercados, deben revisar constantemente sus planes de producción, respaldados por estrategias que permitan mayores ganancias y rentabilidad (Romanzinil et al, 2017). Llevar a cabo una planificación de producción permite a las empresas mejorar su preparación y agilidad para enfrentar las turbulencias del mercado (Andres et al, 2017). La correcta selección de esta herramienta es de gran utilidad al incrementar los indicadores de producción, elevar el servicio que las mismas brindan al cliente (Tamayo y Urquiola, 2014) y emplear de manera más eficiente los recursos, sin afectar la calidad de los productos (Moreno y Reyes, 2015).…”
Section: Figuraunclassified
“…In a distributed manufacturing environment, manufacturing equipments and individual agents may be in various geographical locations, and the manufacturing capacity of resources should be taken into account together with the synergy between transportation and production. The coordination of production and transportation is common in steel manufacturing, automotive sector suppliers and other industries [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the city of Neiva, as a region in the way of technological, industrial and economic development, presents a series of its own characteristics, evidenced by the culture, norms and customs present in its inhabitants and that influence the way of doing business or manage an organization. The study indicated that 44.5% of the companies in the city concentrate their time and resources in controlling sales due to a large extent and as indicated by [10], [11]. Which isn't counted within the organizations with the interest of knowing their own processes; nor are there any tools that identify their relevant variables, so that improvements cannot be applied or adequate information can be acquired to make timely decisions that result in better production, greater sales.…”
Section: Introductionmentioning
confidence: 99%